Electrochemical reaction of CO2 to CO on a catalyst coated cation exchange membrane enabled by ammonium proton shuttling. Issue 19 (18th August 2022) - Reinisch, D.; Reichbauer, T.; Vetter, K. M.; Martić, N.; Mayrhofer, K. J. J.; Schmid, G.
Abstract : CO2 reduction (CO2 RR) can convert CO2 into feedstock for the chemical industry. In a novel operation mode NH4 + ions locally buffer the pH on a cation exchange membrane (CEM) and thereby enable efficient CO2 RR on an Ag-coated CEM cathode. Abstract : CO2 reduction (CO2 RR) can convert CO2 into feedstock for the chemical industry. In aqueous CO2 electrolysis a key challenge is how to combine the CO2 educt with a neutral or alkaline electrolyte and achieve a stable cell operation. We propose a novel cell design and operation mode based on a catalyst coated cation exchange membrane: a cationic acid (NH4 + ), with a volatile conjugate base (NH3 ), replaces the protons usually present for ion transport. The approach avoids a high proton concentration at the cathode catalyst while still removing all products within the gas phase. In this paper different cell concepts are investigated to identify a pathway to a stable, efficient and scalable operation mode. In a completely novel cell design a FECO > 50% was already maintained for over 35 h at 50 mA cm −2, and at 200 mA cm −2 a cell voltage of 3.6 V (FECO > 60%) was achieved. Surprisingly, ammonium oxidation at the anode was fully supressed under the reaction conditions.